Erector spinae plane block as part of a multimodal analgesic approach in an anaesthetised horse undergoing dorsal spinous process ostectomy and desmotomy. Issue 2 (14th March 2022) - Rodriguez, Alfonso; Medina‐Serra, Roger; Lynch, Nicola; Veres‐Nyeki, Kata
Abstract: A 14‐year‐old Irish sport horse presented to our institution with a history of right forelimb lameness and left‐sided back pain. Radiography and nuclear scintigraphy were performed under sedation and the horse was diagnosed with overriding dorsal spinous processes, also known as kissing spine syndrome. Surgical treatment consisted of dorsal spinous process ostectomy and desmotomy under general anaesthesia. This case report summarises the perianaesthetic management, which included an erector spinae plane block as part of a multimodal analgesic approach.